Colitis and cancer: a tale of inflammatory cells and their cytokines - Burstein, Ezra; Fearon, Eric R. (The Journal of Clinical Investigation, 2008)
Chronic inflammatory disorders are often associated with an increased cancer risk. A particularly striking example of the chronic inflammation–cancer link is seen in inflammatory bowel disease, in which chronic colitis or persistent inflammation in the colon is associated with elevated risk of colorectal cancer. Animal models exploring the mechanisms by which inflammation increases the risk of colon cancer have shown that inflammatory cells, through the effects of the cytokines they produce, have a major role in promoting neoplastic transformation. In this issue of the JCI, Popivanova and colleagues demonstrate that TNF-α, through its effects on the immune system, plays a critical role in promoting neoplastic transformation in this setting (see the related article beginning on page 560). Importantly, the study also provides evidence that anti–TNF-α therapies, which are currently in clinical use, may interrupt the process.